(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2023)
This thesis statement is about how to make effective lesson plan. While making lesson plan the instructor should pay attention to include all 4 skills, because integrated skills motivates learners to learn language deeply and with curiosity.